Novo sistema in situ para análise da proteólise muscular esquelética: papel da via do AMP cíclico - Bergantin, Leandro Bueno [UNIFESP] (2010)
In vertebrates, skeletal muscle contributes to the control of body energy homeostasis by providing amino acids generated from protein breakdown. However, continued muscle protein breakdown results in muscle atrophy, such as those associated with aging, muscle wasting or neuromuscular dysfunction. The molecular mechanisms involved in regulation of muscle proteolysis as well as the pharmacological screening of drugs that interfere in this process have been addresses by measurement of tyrosine release from muscles of prepubertal rats, because they are thin enough to allow an adequate diffusion of oxygen and substrates under in vitro conditions. Therefore, the effect of aging or neurodegenerative diseases has been analyzed only with static markers, as atrogin-1/MAFbx or Murf-1. The aim of the present study was the establishment of a new in situ experimental model for the dynamic measurement of proteolysis in adult rat muscles, by quantifying the release of tyrosine from the lumbricalis muscle. In addition, the fluorimetric macromethod for tyrosine measurement was adapted for 96 wells microplate, which resulted in 90% reduction in the formation of toxic chemical waste. The results were complemented by analyzing the effect of modulators of Gs protein / adenylyl cyclase / cyclic AMP signaling pathway on proteolysis of adult muscles, whose influence had already been demonstrated in muscles from prepubertal rat. Using adult rat lumbricalis muscle, we found that modulators of the cAMP signaling pathway inhibit muscle proteolysis under basal or catabolic condition induced by denervation. â-adrenergic agonists isoproterenol (30-100 mM; non-selective) and formoterol (1-10 nM; selective â2), the adenylyl cyclase activator forskolin (30-100 nM) and nonselective phosphodiesterase inhibitor IBMX (100-1000 mM) reduced by 12% to 20% muscle proteolysis. Furthermore, our results show that muscle proteolysis in pre-pubertal rats (30 days old) is 94% higher than in adult animals, which makes questionable the direct extrapolation of results obtained from pre-pubertal muscles to adult or senile muscles. The use of lumbricalis muscle as an proteolysis experimental model reduces by 75% the number of animals in proteolysis experimental protocols and by 90% the amount of chemical waste produced, due to the adjustment of the dosage of tyrosine to 96 well microplate, optimizing the pharmacological screening of drugs for anticatabolic purposes.